2021
DOI: 10.2991/assehr.k.210325.013
|View full text |Cite
|
Sign up to set email alerts
|

Needs Analysis: E-Learning-Based of Intensive Reading with Moodle Application

Abstract: The current intensive reading instruction is predominantly teacher-controlled and textbook-bound, finding it challenging for students to take develop of their own learning and to find learning opportunities to practice. Moodle e-learning as one of the selected learning management system will be used to solve these learning problems. This study aims to evidently identify major gaps and the needs of Moodle elearning by the students and lecturer in learning process of intensive reading class. Descriptive method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…The findings revealed that using computer tools and related software is advantageous for the learners. Satriani and Zaim (2021) aimed to investigate the need for Moodle e-learning tools for students and teachers in intensive reading classes in Indonesia. The findings revealed that learners showed their need and interest to change the intensive reading material by using smart media such as Moodle readers.…”
Section: Perceptions Of Learners About the Use Of Technology In The I...mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings revealed that using computer tools and related software is advantageous for the learners. Satriani and Zaim (2021) aimed to investigate the need for Moodle e-learning tools for students and teachers in intensive reading classes in Indonesia. The findings revealed that learners showed their need and interest to change the intensive reading material by using smart media such as Moodle readers.…”
Section: Perceptions Of Learners About the Use Of Technology In The I...mentioning
confidence: 99%
“…Participants also showed their interest that teachers should implement e-learning to improve their reading proficiency. These technologyoriented intensive reading activities can bring about visible improvement in the reading comprehension, vocabulary, grammar, and reading strategies of the learners (Satriani and Zaim, 2021;Du and Liang, 2021;Sun and Tian, 2020).…”
Section: Perceptions Of Learners About the Use Of Technology In The I...mentioning
confidence: 99%
“…In Reading courses, multimedia technology such as Moodle e-learning has been frequently employed, but still a few in intensive reading class because Moodle elearning in the Intensive Reading course is commonly utilized to illustrate of linguistic and it is not focus on use of language. As stated by [2] there are four primary reasons for utilizing e-learning Moodle in the learning process nowadays. First, there is a need for appealing, current learning material that can inspire students to learn.…”
Section: Intensive Reading Course With Moodlementioning
confidence: 99%
“…The use of a learning management system (LMS) such as Moodle has altered way people think about content and class activities especially education world. According to [2], students need to updates the learning process of Intensive Reading, which allows them to learn anywhere and anytime with the support of technology such as e-learning Moodle. This research seeks to see if the Moodle application is effective for Intensive Reading Courses and to get feedback from students who use Moodle in learning Intensive Reading.…”
Section: Introductionmentioning
confidence: 99%
“…Gedik, N., Kiraz, E, & Ozden (2013) ; (Dahalan, N., Hasan, H., Hassan, F., Zakaria, Z. & Noor, W., A., W., 2013), (Satriani et al, 2021a), (Satriani, 2021) menegaskan bahwa dalam membangun e-learning dalam kegiatan pembelajaran, seorang perancang kebutuhan pembelajaran untuk menentukan elemen utama konten desain untuk meningkatkan pembelajaran peserta didik. Dalam merancang e-learning yang diusulkan, beberapa studi yang relevan dianalisis untuk mendukung model baru yang dikembangkan dan kemudian mengenali kelebihan dan kekurangannya.…”
unclassified